Phytochemical screening and analgesic activity of ethanolic extract of Spondias pinnata (L.f.) Kurz "Libas" leaves. - Gaurana, Rnie Shayne Guillermo
Spondias pinnata is one of the traditional medicinal plants which have been identified as a high priority bioresource. Based on its ethomedical information, the leaves of this plant are traditionally used in treating various diseases associated with pain (i.e. burns, sores and wounds). Despite these ethomedicinal claims, scientific studies verifying its analgesic effects are not yet established. Thus, this present study was designed to investigate the analgesis activity of the ethanolic extract of Spondias pinnata leaves in acetic acid-induced writhing test. The ethanolic extract was administered orally at doses of 100 mg/kg, 250 mg/kg and 500 mg/kg on white mice and the mean number of writhing generated was compared with the standard analgesic drug mefenamic acid (250 mg/kg, p.o) in a dose dependent manner. The results showed that the 250 mg/kg and 500 mg/kg dose of extract exhibited high analgesic activity (P<0.0001) by significantly decreasing the number of writhing constrictions in mice and increasing the percent inhibition by 85.09 percent and 85.71 percent, respectively. On the other hand, there was no significant difference in the number of writhing produced between the 100 mg/kg dose of extract and the mefenamic acid. The 100 mg/kg dose of extract showed 36.65 percent inhibition which was comparable with that of the mefenamic acid having 31.68 percent inhibition. Therefore, the study confirmed the analgesic effect of the ethanolic axtract of S. pinnata leaves and hence provided scientific basis on the folkloric use of this plant as an analgesic. Furthermore, qualitative phytochemical screening of extract revealed the presence of the following phytochemicals: alkaloids, glycosides, steroids and triterpenoids, flavonoids, saponins, phenols, and tannins.